Speciation of phosphorus in a fertilized, reduced-till soil system: in-field treatment incubation study - Khatiwada, Raju; Hettiarachchi, Ganga M.; Mengel, David B.; Fei, Mingwei (My University, 2013)
Phosphorus management in reduced-tillage systems is a great concern for farmers. Conclusive positive results of deep-banding P fertilizers compared with broadcast application and the chemistry of reduced-tillage systems remain unclear. Knowledge of the dominant solid P species present in soil following application of P fertilizers and the resulting potential P availability would help us understand and efficiently manage P in reduced-tillage systems. The objective of this research was to study the influence of placement (broadcast vs. deep-band P), fertilizer source (granular vs. liquid P), and time on the reaction products of P under field conditions. Changes in soil pH, resin-extractable P, total P, and speciation of P were determined at different distances from the point of fertilizer application at 5 wk and 6 mo after P application at a rate of 75 kg ha−1 to a soil system that was under long-term reduced tillage. Resin-extractable P was lower for broadcast treatments compared with deep-band treatments for both time periods. Resin-extractable P was greater in the liquid P-treated soils than in the granular P-treated soils. Speciation results showed that granular P fertilizers tended to form Fe–P-like forms, whereas liquid forms remained in adsorbed P-like forms in the soil 5 wk after application; moreover, speciation results showed granular P fertilizers precipitated less when deep-banded. During the 6-mo period following application, reaction products of broadcast granular, broadcast liquid, and deep-band granular fertilizers transformed to Ca-phosphate or mixtures of Ca-, Fe- and adsorbed-phosphate-like forms, whereas deep-band liquid P remained as mainly adsorbed P-like forms. Deep-banding of P would most likely provide a solution that is both agronomically and environmentally efficient for reduced-till farmers.
Citation: Khatiwada, Raju, Ganga M. Hettiarachchi, David B. Mengel, and Mingwei Fei. “Speciation of Phosphorus in a Fertilized, Reduced-Till Soil System: In-Field Treatment Incubation Study.” Soil Science Society of America Journal 76, no. 6 (2012): 2006–18. https://doi.org/10.2136/sssaj2011.0299.
Keywords: Phosphorus; Reduced-till soil systems; Fertilizer